HUBUNGAN TINGKAT PENGETAHUAN TERHADAP PERILAKU SWAMEDIKASI OBAT ANALGESIK, MASYARAKAT RW 04 DESA TREMBULREJO BLORA PERIODE APRIL TAHUN 2021 - Melizsa - Melizsa; Siti Novy Romlah; Istikholul Laiman (Sekolah Tinggi Ilmu Kesehatan Widya Dharma Husada Tangerang, 2022)
Self-medication or self-medication is a community effort in dealing with complaints of illness. In practice, self- medication will cause drug-related problems, this is due to a lack of understanding about drugs and functions. The level of knowledge is one of the factors that facilitate proper self-medication behavior. Analgesics area a class of drugs to treat mild to severe pain. This study aims to determine the relationship between the level of knowledge on self-medication behavior of analgesic drugs in RW 04 Trembulrejo village. This research is an analytical survey research with cross sectional technique. Sampling used non-random sampling with purposive sampling technique. The sample used in this study was 163 respondents. The result of this study indicate that respondents have less knowledge of 11,04%, 72,40% of respondents are classified as good enough, and 16,56% are classified as good. Then the behavior of self-medication showed that 2,45% pf respondents had self-medication behavior classified as lacking, 67,49% of respondentswere classified as moderate, and29,45% were classified as good. Based on the Spearman rank correlation test, there was a significant correlation with the calculated r value of 0,516 and the p value of 0,000 which showed that there was a fairly strong and significant relationship between the level of knpwledge on self-medication behavior of analgesic drugs and the direction of the positive relationship.